Factors Affecting Indonesian Nurse Behavior in Applying Universal Precaution - Wansuzusino, Wansuzusino (University of Muhammadiyah Semarang, 2019)
Professional nurses in carrying out their roles and functions on a daily basis, are always at risk of contacting various diseases. Transmission of the disease can occur via direct or indirect contact, transmission can be through droplet transmission, and airborne transmission (CDC). Universal precautions are one of the strategies that have been recommended by the Centers for Disease Control and Prevention (CDC) in efforts to control infection and disease transmission in health facilities, such as hospitals, doctors' practices, and other health care centers. The purpose of the study was to determine the factors that influence the behavior of Indonesian nurses in implementing universal precaution in the Center for Health Services in Qatar. The research process was carried out in October 2011 in Qatar with a total sampling method, a total sample of 52 respondents. The results showed that most Indonesian nurses in Qatar with a Diploma in Nursing, had work experience of more than 6 years. Placed in various locations such as; ambulance services, company clinics and hospitals. There was no significant relationship between knowledge and nurses behavior in applying Universal Precaution (p <0.05). There was no significant relationship between attitude and behavior of Indonesian nurses in implementing Universal Precaution (p <0.05). There was no significant relationship between motivation and the behavior of Indonesian nurses in implementing Universal Precaution (p <0.05). There was a significant relationship (p <0.05) between the means and the behavior of Indonesian nurses in implementing Universal Precaution. Based on these results it is necessary to maintain the consistency of nurses to always apply universal precaution appropriately according to the patient's condition at hand